The economic and distributional impacts of an increased carbon tax with different revenue recycling schemes - Kelly C. De Bruin; Eoin Monaghan; Aykut Mert Yakut (The Economic and Social Research Institute (ESRI), 2019)
This study finds that a carbon tax could have some adverse impacts on GDP, inequality and household income. However, the impact is limited and could be reduced by using a well-designed revenue recycling scheme. The results come from research using the ESRI's environment, energy and economy (I3E) model for Ireland.
Keywords: 330